Fiscal policy in an Islamic economy and the role of Zakat - Yusoff, Mohammed (International Islamic Universiry Malaysia, 2006)
This study incorporates Zakat into a simple macroeconomic model of an Islamic economy and analyzes the role of Zakat in the national income determination. The reduced form aggregate consumption function suggests that the determinants of consumption are: Zakat expenditure, taxes, income, and asset holdings of individuals. Zakat could be used as a counter-cyclical policy through the discretionary and non-discretionary fiscal policy. The discretionary fiscal policy is carried out by varying the disbursement of Zakat to the recipients. During the expansion phase of the business cycle the government reduces Zakat expenditure to close the inflationary gap. This action helps increase the Zakat surplus in the Baitul-Mal. Likewise the Zakat expenditure could be increased, by using the Zakat surplus accumulated during the boom periods, when the economy is in the down-swing to spur aggregate spending and economic activities. Therefore government spending and taxation could complement Zakat as stabilization policy.